Uma análise comparativa entre a técnica de chaveamentos corretivos e o redespacho de geração em sistemas de potência - Souza, Elton Pereira de (2022)
Faced to changes in energy matrix composition and the gradative increase in demand for electric energy, studies about techniques to mitigate overload in transmission lines are stimulated. Regarding the overload in transmission lines, the Generation Redispatch is considered as the most widespread solution. However, the Corrective Switching technique stands out by reduced execution time and less operational costs when compared with Generation Redispatch. In this sense, this paper is focused to establish a comparison between both techniques, presenting their feasibility and validating the results obtained with the IEEE realiability test system. In a first step, the methodology developed for Corrective Switching selects promising variants in order to eliminate the overload without results in others transmission lines overloads. In a second step, for Generation Redispatch methodology, the Newton’s method is considered to reach the system optimal operating point in order to minimize the transmission lines loading. Therefore, using Scilab (version 6.0.2) as a programming software, these techniques will be executed in order to compare their results.